Role of I.T.M. in human resource development in Malaysia / Mohd. Mansor Salleh - Salleh, Mohd. Mansor (1992)
The role of an organizational entity in human resource development (HRD) encompasses two levels: micro and macro. At the micro level, like any other organization, Institut Teknologi MARA (I.T.M.) has its own human resources to be managed and developed in order to satisfy I.T.M.'s very own organizational objectives. Being part of a dynamic nation, I.T.M. is not divorced of some expected roles within that larger national framework of development. This paper discusses I.T.M.'s role in developing its immediate human resources and in contributing to the national human resource development.